HUKUMAN PELAKU PERKOSAAN DIBARENGI PEMBUNUHAN OLEH ANAK DITINJAU DARI HUKUM POSITIF DAN HUKUM ISLAM (Study Analisis Keputusan Pengadilan Negeri Curup Nomor 7/Pid.Sus.Anak/2016/Pn.Crp) - Heriansyah, Heriansyah (UIN Fatmawati Sukarno Bengkulu, 2018)
This research raises the issue of punishment imposed by the judges on Curup District Court Number 7 / Pid.Sus. Anak / 2016 / PN.Crp to the child as the perpetrator of rape accompanied by the murder of the child victim. The purpose of this research is to know the punishment and basic consideration of judges panel then reviewed from positive law and Islamic law. This research uses normative juridical legal method, with approach of Act, case approach and conceptual approach. The method of collecting legal material used is literature study and documentary study then analyzed by normative descriptive. From the results of research shows that the implementation of criminal punishment for perpetrators of rape coupled murder of children in terms of positive law can be implemented by the panel of judges by applying Article 81 paragraph (1) of Law RI.35 Year 2014 About Amendment to Law no. 23 of 2002 in conjunction with Article 76D of RI Law. 35 of 2014 on Amend- ment to Law No. RI. Article 55 Paragraph (1) and (2) of the Indonesian Criminal Code and Article 80 Paragraph (3) of RI Law No. 23 Year 2002 on Child Protection jo Article 55 Paragraph (1) of the Criminal Code jo Article 65 Paragraph (1) and (2)35 Year 2014 About Amendment to Law no. Law No. 23 Year 2002 on the Protection of Children in conjunction with Article65 Paragraph (1) and (2) of the Criminal Code are cumulative. Whereas in Islamic law the perpetrator may be subjected to a more severe crime (murder) which is the murder in which the perpetrator is assumed to have committed intentional murder with the punishment of the principal in the form of diat and kafarat, the substitution of ta’zir and the additional punishment of the inheritance and will. Based on the decision of the Curup District Court Number 7 / Pid.Sus.Anak / 2016 / PN.Crp that the perpetrators of rape are found to have proven legally and convincingly guilty of intercourse with him or with others and place, let, participate in violence against children who causing the child to die so that the imprisonment is imposed for 10 (ten) years and the training of each work for 6 (six) months. According to Islamic law the offender may be punished by paying diyat to the heirs of 100 (one hundred) camels or 200 (two hundred) cows or 2000 (two thousand) goats, freeing a slave or fasting two months in a row and ta’zir